Penerapan Basic Life Support Pada Relawan Dalam Tanggap Darurat - Widyastuti, Merina; Setiadi; Dwi Priyantini; Nur Muji Astuti; Suharsono, Tony (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2020)
This community service activity aims to see the effects of audio-visual simulation methods in increasing the knowledge and skills of volunteers about basic life support. In this case the method carried out by volunteers is given a pre test on basic life assistance, then given material about the concept of disaster in the emergency response phase and simulation of basic life assistance through audio visual. The material is given for 1.5 hours and then the participants are divided into groups and given a simulation of providing basic life assistance for 1.5 hours and then the participants try to practice according to the basic life assistance algorithm. After completing the simulation the participants were given a post test link online. The results of the achievement of this implementation that there has been a change in knowledge shown by volunteer simulations in conducting basic life support. This is evident from the significant percentage increase assessed from the results of volunteer responses after the training was given. Some of the parameters we value are the initial assessment when finding victims and the steps in providing basic life assistance. Thus it can be concluded that the audio visual simulation method of providing basic life assistance is considered to be quite effective in increasing the ability of volunteers to play a role in the stages of disaster emergency response.